Business intelligence and contribution of entrepreneurial information architecture - Fernandes, Silvia Brito (2013)
We are witnessing the need for a quick and intelligent reaction from organizations to the level and speed of change in business processes. The arising problems can be: from wrong lasting information; systems not fully used or explored; slow reaction to change; etc. This requires two main confluent action methods: people to synchronize their visions, ideas and strategies in the whole organization; and, in that context, select the information that strictly answers to the performance factors at the right moment. The proposed methodology turns to the potential of approach to the entrepreneurial architecture as well as to the potential of the information system in order to integrate the data and resources needed for that performance. The modeling of an information architecture of the company and its business helps in the identification of critical information, the one which is according to the mission, prospects and business success factors.